Incidence and risk factors for clinically diagnosed knee, hip and hand osteoarthritis: influences of age, gender and osteoarthritis affecting other joints. - Prieto-Alhambra, D; Judge, A; Javaid, M; Cooper, C; Diez-Perez, A; Arden, N (BMJ Publishing Group, 2014)
OBJECTIVES: Data on the incidence of symptomatic osteoarthritis (OA) are scarce. We estimated incidence of clinical hip, knee and hand OA, and studied the effect of prevalent OA on joint-specific incident OA. METHODS: SIDIAP contains primary care records for>5 million people from Catalonia (Spain). Participants aged ≥40 years with an incident diagnosis of knee, hip or hand OA between 2006 and 2010 were identified using International Classification of Diseases (ICD)-10 codes. Incidence rates and female-to-male rate ratios (RRs) for each joint site were calculated. Age, gender and body mass index-adjusted HR for future joint-specific OA according to prevalent OA at other sites were estimated using Cox regression. RESULTS: 3 266 826 participants were studied for a median of 4.45 years. Knee and hip OA rates increased continuously with age, and female-to-male RRs were highest at age 70-75 years. In contrast, female hand OA risk peaked at age 60-64 years, and corresponding female-to-male RR was highest at age 50-55 years. Adjusted HR for prevalent knee OA on risk of hip OA was 1.35 (99% CI 1.28 to 1.43); prevalent hip OA on incident knee OA: HR 1.15 (1.08 to 1.23). Prevalent hand OA predicted incident knee and hip OA: HR 1.20 (1.14 to 1.26) and 1.23 (1.13 to 1.34), respectively. CONCLUSIONS: The effect of age is greatest in the elderly for knee and hip OA, but around the menopause for hand OA. OA clusters within individuals, with higher risk of incident knee and hip disease from prevalent lower limb and hand OA.